Pengaruh Pemberian Pupuk NPK Phoska dan Pupuk Organik Cair Terhadap Pertumbuhan dan Produksi Tanaman Pisang Rutai ( Musa sp ) - Teguh Martono; Purwati Purwati; Iin Arsensi (Universitas Widya Gama Mahakam, 2017)
The Influence of NPK Phoska Fertilizer and Liquid Organic Fertilizer on Banana Plant Growth and Production (Musa sp). The purpose of this study was to determine the effect of NPK Phoska fertilizer and liquid organic fertilizer on the growth and production of banana rutai plant. The study was conducted for 7 (seven) months, from February to September 2015, starting from land preparation to data collection. This research was conducted on campus of Widya Gama Mahakam Samarinda. The research design used was factorial randomized block design 3 x 3 with 3 times replication. The first factor was Phoska NPK fertilizer (P) consisting of 3 levels: P0 (Without Treatment), P1 (1080 g / plant) and P2 (1580 g / plant). The second factor is the application of liquid organic fertilizer (B) 3 levels, namely: B0 (Without treatment), B1 (5000 ml) and B2 (10000 ml). The result of the research showed that the best treatment of NPK Phoska P2 (1580 g / plant) was the average of plant height 90 days after the highest treatment was 122.33 cm, the largest mean stem diameter was 11,08 cm and average the highest number of comb per bunches is 7.22 comb, the fastest harvest age is 248 days after planting. The best treatment of liquid organic fertilizer to the average number of combs per cluster was achieved at the treatment of B1 (5000 ml) ie 5.33 comb, the fastest harvest age 248 days after planting. The interaction between NPK Phoska fertilizer application and liquid organic fertilizer did not significantly affect all observation parameters.